Peri-implant soft tissue conditioning of immediate posterior implants by CAD-CAM socket sealing abutments: a randomized clinical trial - Mai Mohamed Elgendi; Iman Salah Eldin Hamdy; Hanaa Ibraheem Sallam (BMC Oral Health)
Abstract Background Anatomically formed healing abutments were suggested in literature to address many of the issues associated with immediate posterior implant insertion such as large extraction sockets that are extremely hard to seal without reflecting the mucoperiosteal flap, extraction sockets anatomy that are not suitable for regular healing abutment placement, and potentially high occlusal stresses when planning a temporary implant supported prothesis to improve the conditioning of supra implant tissue architecture and the emergence profile of the implant supported restorations. Purpose To clinically evaluate the peri-implant soft tissue profile of single posterior implant retained restorations and to assess patient related outcomes of the implant restorations that were conditioned immediately by CAD-CAM socket sealing abutments (SSA) versus those conditioned by Titanium (Ti) standard healing abutments (SHA). Methods Twenty participants received twenty-two single maxillary immediate implants after flapless minimally invasive tooth extraction and 3D guided implant placement in the posterior area (premolar and molar) and allocated randomly into two groups (n = 11), the intervention group: patients received PEEK SSA and the control group: the patients received Ti SHA. Modified Pink Esthetic Score (PES) was evaluated at 3 observation periods: Baseline T0 (immediate after implant supported crown insertion), 6 months T1 and 1 year of clinical performance T2. Patient satisfaction was assessed one week and one year after crown insertion using visual analogue scale (VAS). Results At base line, after six as well as 12 months, SSA group showed statistically significant higher total modified PES scores than SHA group (P-value < 0.001). At the 2 clinical observation periods (baseline and after one year), SSA group showed statistically significantly higher overall satisfaction score than SHA group (P-value < 0.001). Conclusion After one year of clinical observation period, CAD-CAM PEEK socket sealing abutments together with flapless minimally invasive tooth extraction and 3D guided implant placement provided superior outcomes compared to Ti SHA in terms of peri-implant soft tissue profile. Trial registration This study was registered on clinicaltrials.gov with ID no. NCT05276765 on 03/03/2022.